Adverse event profiles of EGFR-TKI: network meta-analysis and disproportionality analysis of the FAERS database - Shi, Jing; Liu, Xinya; Gao, Mengjiao; Yu, Jian; Chai, Ting; Jiang, Yun; Li, Jiawei; Zhang, Yuanming; Wu, Li (Frontiers in Pharmacology, 2025)
BackgroundEpidermal Growth Factor Receptor Tyrosine Kinase Inhibitors (EGFR-TKIs) in clinical use show promise but can cause AEs, impacting patients’ wellbeing and increasing costs.MethodsThis study utilized two methods: network meta-analysis (NMA) and disproportionality analysis (DA). For NMA, we searched PubMed, Embase, Cochrane Central Register of Controlled Trials, and ClinicalTrials.gov up to 10 September 2024, for phase II/III RCTs comparing EGFR-TKI monotherapy with chemotherapy or other EGFR-TKIs. Using STATA 18.0, we calculated odds ratios (ORs) with 95% confidence intervals (CIs) and assessed heterogeneity via Chi-squared and I2 tests. Adverse events (AEs) were ranked using the surface under the cumulative ranking curve (SUCRA). For DA, we analyzed FAERS data (January 2004-June 2024), evaluating AE signals with reporting odds ratios (RORs) and 95% CIs; signals were considered significant if the ROR and its 95% CI lower bound exceeded 1. Primary outcomes for NMA included all-grade AEs, grade ≥3 AEs, specific AEs, and AE-related mortality. For DA, outcomes included EGFR-TKI as the primary AE cause, time from treatment to AE, and AE-related mortality.ResultsNMA: 48% of EGFR-TKI patients experienced AEs, with 32.7% being severe. Afatinib showed highest toxicity; Icotinib was safest. Osimertinib was associated with highest risks of leukopenia (8%) and thrombocytopenia (9%). DA: Osimertinib had strongest links to cardiac diseases and blood/lymphatic disorders. Gefitinib had the strongest signal for interstitial lung diseases; Erlotinib for anorexia. Most AEs occurred within 30 days, but cardiac disorders had a median onset of 41 days. Osimertinib had the highest AE-related mortality, with cardiac disorders leading in fatalities.ConclusionThis study used NMA and DA to explore EGFR-TKI-related AEs. Drugs varied in AE profiles, mostly mild, but Osimertinib and Dacomitinib were associated with more severe events. Osimertinib carried a high cardiac risk, delayed onset, and high mortality. Thus, comprehensive patient assessment and close monitoring are crucial with EGFR-TKI use.